2017
DOI: 10.1371/journal.pntd.0004958
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus ducreyi DNA is detectable on the skin of asymptomatic children, flies and fomites in villages of Papua New Guinea

Abstract: BackgroundHaemophilus ducreyi and Treponema pallidum subsp. pertenue are major causes of leg ulcers in children in Africa and the Pacific Region. We investigated the presence of DNA (PCR positivity) from these bacteria on asymptomatic people, flies, and household linens in an endemic setting.Methodology/Principal findingsWe performed a cross-sectional study in rural villages of Lihir Island, Papua New Guinea during a yaws elimination campaign. Participants were asymptomatic subjects recruited from households w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
3
28
1
Order By: Relevance
“…The choice of case-control study design could amount to recall bias particularly among the controls. Also, swabs from yaws-like ulcers in some endemic areas have shown infections with Haemophilus ducreyi alone or coinfections with T. pallidum subspecies pertenue and H. ducreyi [9,11,16,17,29]. The prevalence of substandard sanitary and personal hygienic conditions in yaws-endemic communities also facilitates the persistence of H. ducreyi infections in these communities [29].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of case-control study design could amount to recall bias particularly among the controls. Also, swabs from yaws-like ulcers in some endemic areas have shown infections with Haemophilus ducreyi alone or coinfections with T. pallidum subspecies pertenue and H. ducreyi [9,11,16,17,29]. The prevalence of substandard sanitary and personal hygienic conditions in yaws-endemic communities also facilitates the persistence of H. ducreyi infections in these communities [29].…”
Section: Discussionmentioning
confidence: 99%
“…ducreyi DNA on the skin of asymptomatic participants, on flies, and on bed sheets, suggesting that H . ducreyi survives on healthy, nongenital skin where even minor trauma could initiate infection [ 11 ]. In addition, these cases with HD-CU after a minor trauma could indicate that H .…”
Section: Discussionmentioning
confidence: 99%
“…Transmission is skin to skin contact from active infectious lesions [ 14 ]. Early studies had suggested that flies may play a role in transmission but there is no definitive proof that this occurs [ 14 , 15 , 16 ]. The majority of active infections cases occur in children aged under 15 years.…”
Section: Epidemiologymentioning
confidence: 99%